HUBUNGAN DURASI RIWAYAT PEMBERIAN ASI TERHADAP KEJADIAN DIARE PADA BAYI - Muji Basailin; Agrina Agrina; Reni Zulfitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Exclusive breastfeeding reduces infant mortality due to common childhood illnesses such as diarrhea. This study aimed to determine the correlation between breastfeeding and diarrhea on infants. A cross-sectional correlation research design was used for this study, with a total 87 mothers of the babies aged 6 – 12 months were selected by purposive sampling technique at Rejosari Health Center. The measuring tool used is a questionnaire that has been tested for validity and reliability. Conducting Univariate and Bivariate analysis using Chi-square testing, the data results shows the babies given ASI exclusive for 6 months as many as 39 babies (44.8%), while babies that were breastfed under 6 months (non-exclusive breastfeeding) is up to 48 babies (55.2%). Along with this, reportedly 39 breastfed infants less than 6 months (81.3%) had diarrhea, and only13 exclusive breastfed infants (33.3%) who had diarrhea. The result of analyzing bivariate on P value 0,000 reveal that breastfeeding duration were significantly associated with Incidence of Diarrhea. This research suggested to all mothers to give exclusive breastfeeding to protect children against illness and disease especially diarrhea. Keywords: Breastfeeding, Diarrhea, Infant